Pengaruh Electronic Word of Mouth (E-Wom) dan Kualitas Pelayanan terhadap Kepercayaan Konsumen pada Patuha Resort Bandung - Donny Purwoko; Zaharuddin Zaharuddin; Sitta Kusuma Freddy (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The rapid growth of digital platforms has transformed consumer behavior in the tourism industry, particularly in the way trust is formed through online information and service experiences. In nature-based resorts, consumer trust is influenced not only by direct service encounters but also by perceptions generated through Electronic Word of Mouth (E-WOM). This study aims to examine the effect of Electronic Word of Mouth (E-WOM) and service quality on consumer trust at Patuha Resort Bandung, both partially and simultaneously. This research employed a quantitative approach with descriptive and associative designs. The population consisted of consumers of Patuha Resort Bandung, and a sample of 100 respondents was determined using the Slovin formula. Data were collected through structured questionnaires using a five-point Likert scale and analyzed using multiple linear regression with SPSS version 27. The results show that Electronic Word of Mouth (E-WOM) has a positive and significant effect on consumer trust. Service quality has a positive but statistically insignificant effect when tested partially. However, E-WOM and service quality simultaneously have a significant influence on consumer trust. The findings indicate that E-WOM plays a dominant role in building consumer trust, while service quality functions as a supporting factor that reinforces consumer experience and trust sustainability in tourism services.